Cu2O/CuO Nanoparticle-Cotton Fiber Biocomposite Catalyst: Self-Improvement through Morphological Changes during Methyl Orange Degradation - Hillyer, Matthew B; Jordan, Jacobs H; Ernst, Nicholas E; Nam, Sunghyun; Easson, Michael W (Langmuir, 2024)
In this study, the application of a novel polymer-supported Cu2O/CuO nanoparticle catalyst for the efficient degradation of an organic dye, in which the nanoparticle catalyst is incorporated within a natural plant fiber matrix, is presented. The use of plant fibers provides a renewable and environmentally friendly support material, and enhances the catalytic efficiency over consecutive degradation cycles. This innovative design promotes the efficient adsorption and degradation of dye. The nanoparticle biocomposite showed a remarkable capacity to degrade methyl orange in solution (50 ppm, 150 mL) in <3 h (pH 7.2) or <1.5 h (pH 9.1) using 150 mg catalyst material containing 1.7 wt % copper content. Over five catalytic reaction cycles, the content of Cu1+ relative to Cu2+ increased from 57.6 to 94.1%, average particle size decreased from 54.7 ± 58.5 to 28.7 ± 22.0 nm and the average circularity increased from 0.69 ± 0.25 to 0.75 ± 0.25, while maintaining high catalytic degradation efficiency (>99.6%). The experimental results demonstrate high degradation rates, showcasing the catalyst's potential for sustainable industrial waste remediation applications.In this study, the application of a novel polymer-supported Cu2O/CuO nanoparticle catalyst for the efficient degradation of an organic dye, in which the nanoparticle catalyst is incorporated within a natural plant fiber matrix, is presented. The use of plant fibers provides a renewable and environmentally friendly support material, and enhances the catalytic efficiency over consecutive degradation cycles. This innovative design promotes the efficient adsorption and degradation of dye. The nanoparticle biocomposite showed a remarkable capacity to degrade methyl orange in solution (50 ppm, 150 mL) in <3 h (pH 7.2) or <1.5 h (pH 9.1) using 150 mg catalyst material containing 1.7 wt % copper content. Over five catalytic reaction cycles, the content of Cu1+ relative to Cu2+ increased from 57.6 to 94.1%, average particle size decreased from 54.7 ± 58.5 to 28.7 ± 22.0 nm and the average circularity increased from 0.69 ± 0.25 to 0.75 ± 0.25, while maintaining high catalytic degradation efficiency (>99.6%). The experimental results demonstrate high degradation rates, showcasing the catalyst's potential for sustainable industrial waste remediation applications.